Giant Mucocele of Maxillary Sinus, Scarce Occurrence: Case Report - Srivastava, Dr. Madhumita; Chowdhury, Dr. Sanjoy; Vishal, Dr. Gaurav (Jour Med Resh and Health Sci, 2022)
Mucoceles are common pathology occurring still about paranasal sinuses it is less common and rare for maxillary sinus. Scare to scare is giant mucoceles of the maxillary sinus causing bone destruction in patients with no history of sinonasal surgery. To diagnose sinus pathology one must be well versed with the type of tissue that is present in the normal antrum, as a diseased or pathologic tissue is nothing but a modification of the normal. Here we present one such case of mucocele in the maxillary sinus which reported to us in a quite pronounced state. The mucocele had eroded the surrounding walls of the sinus, so it was essential and challenging to differentiate from malignancy. The case was thoroughly examined, investigated and lastly diagnosed as mucocele and treated successfully.